2007
DOI: 10.1007/s00401-006-0189-y
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitinated pathological lesions in frontotemporal lobar degeneration contain the TAR DNA-binding protein, TDP-43

Abstract: We have investigated the extent and pattern of immunostaining for the TAR DNA-binding protein, TDP-43, in 37 patients with frontotemporal lobar degeneration with ubiquitin (UBQ) pathology (FTLD-U). We confirm that TDP-43 protein is a component of the UBQ immunoreactive (UBQ-ir) neuronal cytoplasmic inclusions (NCI), neuronal intranuclear inclusions (NII) and neurites of the cerebral cortex and hippocampus in FTLD-U. We further show that the same three histological patterns, previously identified by us accordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
217
1
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 280 publications
(232 citation statements)
references
References 36 publications
11
217
1
2
Order By: Relevance
“…Therefore we performed double immunofluorescence to label both ubiquitin aggregates and TDP-43. We found that loss of nuclear TDP-43 staining was occasionally seen in neurons with ubiquitin positive inclusions, similar to what has been reported in human FTLD-U and ALS (20) (Fig. 2 E-G).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Therefore we performed double immunofluorescence to label both ubiquitin aggregates and TDP-43. We found that loss of nuclear TDP-43 staining was occasionally seen in neurons with ubiquitin positive inclusions, similar to what has been reported in human FTLD-U and ALS (20) (Fig. 2 E-G).…”
Section: Resultssupporting
confidence: 89%
“…Cytoplasmic aggregates of TDP-43, together with loss of normal nuclear TDP-43 staining, are a common feature in vulnerable neurons in both FTLD-U and ALS (6,20). However, immunohistochemical analysis of Prp-TDP43 A315T mouse brains using multiple different antibodies to TDP-43 did not show obvious cytoplasmic aggregates or inclusions, despite the striking abnormalities seen with ubiquitin immunostaining shown above.…”
Section: Resultsmentioning
confidence: 86%
“…Nuclear depletion of TDP-43 in Grn-KO retinal neurons precedes neurodegeneration Loss of nuclear TDP-43 is commonly observed in postmortem brain tissue from patients with FTLD-TDP (Neumann et al, 2006;Davidson et al, 2007), including FTLD associated with GRN mutations (Fig. 2 A).…”
Section: Results and Discussion Early Retinal Abnormalities In Humansmentioning
confidence: 99%
“…FTLD-U [6,7]. Recently, the transactive response (TAR) DNA-binding protein 43 (TDP-43) was identified as the major disease protein in UBIs that accumulate in the central nervous system (CNS) of patients with FTLD-U as well as in patients with sporadic and familial ALS [8], but not in the majority of patients with familial ALS (FALS) due to SOD-1 gene mutations [8][9][10][11][12]. These data provided compelling evidence that FTLD-U and ALS represent a clinicopathological spectrum of the same neurodegenerative disorder, i.e.…”
Section: Introductionmentioning
confidence: 99%